Optimizing Platelet GPVI Inhibition versus Haemostatic Impairment by the Btk Inhibitors Ibrutinib, Acalabrutinib, ONO/GS-4059, BGB-3111 and Evobrutinib - Denzinger, Viola; Busygina, Kristina; Jamasbi, Janina; Pekrul, Isabell; Spannagl, Michael; Weber, Christian; Lorenz, Reinhard; Siess, Wolfgang (Thrombosis and Haemostasis, 2019)
Ibrutinib and acalabrutinib are approved for B cell malignancies and novel Bruton's tyrosine kinase (Btk) inhibitors undergo clinical testing also in B cell-driven autoimmune disorders. Btk in platelets mediates platelet activation via glycoprotein (GP) VI, which is crucial for atherosclerotic plaque-induced platelet thrombus formation. This can be selectively inhibited by Btk inhibitors. Since patients on second-generation Btk inhibitors apparently show less bleeding than patients on ibrutinib, we compared the effects of ibrutinib and four novel irreversible Btk inhibitors on GPVI-dependent platelet aggregation in blood and in vitro bleeding time. Low concentrations of collagen which induced the same low degree of GPVI-mediated platelet aggregation as atherosclerotic plaque material were applied. IC50 values for collagen (0.2–0.5 µg/mL)-induced platelet aggregation after 15-minute pre-incubation were: ibrutinib 0.12 µM, BGB-3111 0.51 µM, acalabrutinib 1.21 µM, ONO/GS-4059 1.20 µM and evobrutinib 5.84 µM. Peak venous plasma concentrations of ibrutinib (0.5 µM), acalabrutinib (2 µM) and ONO/GS-4059 (2 µM) measured after anti-proliferative dosage inhibited collagen-induced platelet aggregation, but did not increase PFA-200 closure time on collagen/epinephrine. Closure times were moderately increased by 2- to 2.5-fold higher concentrations of these inhibitors, but not by BGB-3111 (1 µM) and evobrutinib (10 µM). Prolonging platelet drug exposure to 60 minutes lowered IC50 values of any Btk inhibitor for GPVI-mediated aggregation by several fold, and 5- to 10-fold below anti-proliferative therapeutic drug plasma levels. In conclusion, low blood concentrations of ibrutinib and the novel Btk inhibitors suffice for GPVI selective platelet inhibition relevant for atherothrombosis but do not impair primary haemostasis.
Keywords: Btk inhibitor; platelet aggregation; bleeding; PFA; GPVI